RISK FACTORS OF SIMULTANEOUS SURGERY FOR CONCURRENT LUNG CANCER AND CARDIAC VASCULAR DISORDERS - D. G. Kabakov; D. V. Bazarov; M. A. Vyzhigina; B. A. Akselrod; A. A. Morozova; A. A. Kavochkin; Yu. V. Belov (Вестник анестезиологии и реаниматологии, 2018)
Currently, there is a global trend of growing frequency of concurrent lung malignant tumors and cardiac vascular pathology, in particular, ischemic heard disease. The literature review demonstrates, that development of surgery, anesthesiology and intensive care allows expanding limits for treatment of such patients through simultaneous surgery when lungs and heart are operated at the same time.The article analyzes the personal experience of the authors and international publications, it contemplates on safe performance of simultaneous and multi-organ surgeries, involving respiratory and blood circulation systems, different approaches to surgery, its specific features, benefits, and limitations. Specialists from Russian Surgery Research Center named after B.V. Petrovsky find it preferable to perform simultaneous staged surgery of the lungs, mediastinum and cardiac vascular system. There is a certain sequence of stages. It demonstrates that the first stage may include isolation of abnormal masses of the lung (mediastinum) and lung hilus, if necessary. After that cardiac surgery is performed, and as a final stage, the whole abnormal focus is isolated and resected.